Etika dan Hukum Pernikahan dalam Islam: Panduan Menuju Pernikahan yang Harmonis - Indah Amani Lubis; Nurmala Dewi Lubis; Muhammad Amar Adly; Heri Firmansyah (Pusat Riset dan Inovasi Nasional, 2025)
Marriage in Islam is not only seen as a socially legitimate bond, but also as a part of deep worship. The process towards marriage begins with engagement, which contains various ethical and legal values that must be considered by both parties. This article aims to examine the ethics and laws related to engagement in Islam, with a focus on the procedures for engagement, the rights and obligations of prospective husband and wife, and legal views on physical and social attachment during the engagement period. This study concludes that although engagement is not legally binding like marriage, there are moral and social rules that must be respected, including maintaining the honor and boundaries of interaction between prospective husband and wife. This article also highlights the importance of understanding the rights and obligations of each party during the engagement period, which can lead to a sacred and harmonious marriage.